PROCESSING OF COIR A BIOLOGICAL APPROACH TO RETTING OF COCONUT HUSKS - ANITA DAS RAVINDRANATH (International Coconut Community Journal, 1991)
White coir fibre is extracted from coconut husks after 'retting' for a period varying between six to ten months depending upon several environmental factors. With a view to explore the possibility of reducing the prolonged period required for retting and improving the quality of the coir fibre a field study was conducted at Azhikode in the N. Parur regions of Kerala which is a 'poor'* retting area. Selected strains of efficient pectin and phenol degrading bacterial cultures were inoculated into pits containing lots of husks soaked for retting. Samples of husks were analysed at regular intervals for details of degradation of the husk constituents holding the individual fibres together. It was observed that inoculation of the bacterial strains could shorten the period of retting by two and a half months and yield an improved quality of fibre with respect to colour and texture. The detaiis of the experimental field study are presented in this paper.